Profitability, Company Size and Capital Structure: Indicators of Corporate Valuation of Miscellaneous Industry Sectors - Musdafia, Ida; Barus, Yohn Piter; Kinanti, Figih (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
The purpose of this study is to test and examine empirically how capital structure, company size, and profitability affect the value of manufacturing companies in various industries that are listed on the Indonesia Stock Exchange. The focus on firm development and management to optimize company value, especially in the post-pandemic era, and the extension of the research period are what make this study novel. Purposive sampling was utilized to choose ten companies for the research sample, and the data used is the financial statements of the companies. Using a quantitative approach, the research technique analyzes data using descriptive statistical tests, traditional assumption tests (autocorrelation, heteroskedasticity, multicollinearity, and normality), and hypothesis testing using T-tests and F-tests with the aid of eviews 12 software. According to the study's findings, capital structure significantly lowers business value, profitability significantly increases it, and firm size has no discernible impact. All three factors, however, significantly increase business value at the same time. The research's impacts include giving management advice on how to optimize business value and boost investor trust in capital investments.